PENYULUHAN BIMBINGAN BELAJAR MEMBACA BAGI ANAK SEKOLAH DASAR DI DESA FAJAR JAYA (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
This Community Service activity is carried out with the aim of providing understanding, knowledge, and fostering a willingness to learn to read. This is so that students have adequate abilities in reading. Community Service Activities (PkM) were carried out in Fajar Jaya Village, Lengkiti District, Ogan Komering Ulu (OKU) Regency. The steps for implementing this PkM activity are as follows. (1) Observing students' learning experiences. (2) Identifying problems experienced by elementary school children in reading. (3) Providing counseling. (4) Evaluate the results of children's/students' understanding. (5) Improving the comprehension results of elementary school children through reading guidance. Based on the test results, the reading ability of elementary school children in Fajar Jaya village has increased. The average score before being given guidance and counseling, the average ability of these children only reached 65, whereas after providing counseling and guidance, the average reading ability of these children reached 82. This shows that their abilities have increased. More focused reading, better ability to understand reading content, and reading speed at standard level.